Conflicts of Interest at the NIH: No Easy Solution - Resnik, David B. (The Hastings Center report, 2005)
Editor's Note: On February 2, 2005, the National Institutes of Health changed course on conflicts of interest and prohibited its scientists from owning stock in or working as consultants with pharmaceutical or biotechnology companies. The following essay, sent to press before the new policy was announced, recommends a very different approach. The author stands by the recommendations.